Boundary Making in Translation Zones: Analyzing the Differences and Commonalities between Professionals and Volunteers. Issue 3 (August 2022) - Davidovic Walther, Antonia
ABSTRACT: The article discusses practices of cooperation between metal detectorists and professional archaeologists in Germany by exploring the approach of the regional office for historic preservation (Generaldirektion Kulturelles Erbe) in Speyer (Rheinland-Pfalz, southwest Germany). Its model is based on open access to a permit for detecting in a certain area, combined with regular meetings in order to establish knowledge circulation between volunteer and professional spheres. Relying on ethnographic fieldwork and questionnaires, the research shows that the approach creates a symmetric coproduction of knowledge, recognizing the metal detectorists as volunteer researchers producing genuine knowledge. Several theoretical aspects of knowledge circulation are analyzed with regard to their relevance for practices of knowledge production. The enactment of the boundary between public and professionals is the result of boundary work actively performed. As a consequence, this boundary should rather be seen as a fluid, hybrid zone, conceptualized as a translation zone. The concept of boundary objects points to the importance of specific elements for enabling circulation of knowledge between different spheres. Various communities of practice and their shared practices, conventions, perceptions, et cetera, influence the relationship and knowledge circulation, and these should be taken into account in coproduction processes.